Preskrba s stanovanji v dolini Katmanduja - Shrestha, Bijaya K. (Urbani izziv, 2010)
The haphazard growth of settlements in the Kathmandu Valley is the result of rapid urbanisation, growing poverty, the high cost of land and construction, and dependence on the traditional practice of owner-built housing. This growthhas resulted in huge housing deficits and poor home conditions. The government''s implementation of the site and services programme as well as land-pooling projects in the 1970s and 1980s benefitted local landowners, but private-sector developments in the 1990s and 2000s were only accessible to upper-middle and high-income groups. This has forced the urban poor and economically disadvantaged groups to live in slum and squatter developments. Planned development organisation has been weak in terms of physical layout, the creation of socialisation opportunities and a sense of community, and in achieving a desirable population density. The existing legal and institutional framework is inadequate and ineffective for addressing these issues. To fill the gap between the efforts of the public and private sectors and meet the high demands for housing in the valley, clear-cut policies and planning are required. This must be done in order to link housing supply with demand and to ensure the participation of various public and private-sector agencies in land-development and housing projects that will incorporate the urban poor. Local municipalities should also be equipped for managing local resources, coordinating the agencies involved and monitoring development.
Keywords: bivalno okolje; Kathmandu; Katmandu; mesta; naselja; Nepal; revščina; slumi; stanovanja; urbana sociologija; urbanizacija